Collaborative Learning Activities through MoE in Engaging EFL Learners and Diminishing their Foreign Language Anxiety - Fatimah, Sitti (English Language Teaching Educational Journal, 2019)
Mantle of the Expert (MoE) is an approach integrating drama in learning. A number of studies have   proven the approach to be effective in enhancing student?s learning experience and vary teacher?s teaching strategy. This article is drawn from the results of a multi-case study that implemented MoE in  EFL teaching in Indonesia. The study involving three cohorts of Grade 11 Indonesian senior and vocational high school students and three English teachers used multiple data collection methods: classroom observation, questionnaire and interview. While questionnaire was distributed to the student participants, the interview was administered to collect the data from teacher participants. The MoE implementation involved a series of drama activities integrated with the lesson topics. During the activities the student participants were assigned several tasks to be completed in small groups. This required students to collaborate. The findings show that these collaborative learning activities has shown positive major impacts, two of them are students? increased engagement and decreased speaking anxiety.